Cyprus : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper and Statistical Appendix analyzes labor market institutions and reforms for Cyprus. The paper describes the legal and institutional framework of the Cypriot labor market, and discusses the voluntary framework for negotiations, the degree of unionization and the system of tripartism, the wage setting mechanism, and labor market programs. The paper makes an assessment of the flexibility and efficiency of the Cypriot labor market, and in particular, the wage-setting mechanism. It also examines the trends and developments in the external competitiveness of Cyprus.